Find me - Mafi, Tahereh; Adam, Vikas; HarperCollins (Firm) (2019)
Calling all fans of Tahereh Mafi's New York Times bestselling Shatter Me series! In the Shadow Me novella, Juliette is still reeling from Warner's betrayal, and Kenji is trying to balance his friendship with her with his responsibilities as a leader of the resistance against the Reestablishment. Things get even more interesting when an unexpected person from Omega Point's past surfaces. The fourth novella brings readers back to the Shatter Me world one last time before the final novel installment in the series hits shelves in 2020. The Shatter Me series is perfect for fans who crave action-packed young adult novels with tantalizing romance like Divergent and The Hunger Games. This captivating story was praised as "a thrilling, high-stakes saga of self-discovery and forbidden love" by Ransom Riggs, bestselling author of Miss Peregrine's Home for Peculiar Children. And don't miss Defy Me, the gripping fifth book in the Shatter Me series!
Downloadable audio file.
Narrated by Vikas Adam.
12 years and up.
Keywords: Ferrars, Juliette -- (Fictitious character) -- Fiction; Young Adult Fiction; Romance; Science Fiction; Science Fiction & Fantasy; Downloadable audio books; Audiobooks